Ritmata de Edino Krieger: uma reflexão sobre processos vanguardistas na literatura do violão brasileiro - Michel Barboza Maciel (2010)
The main focus of the present work is the piece Ritmata by Edino Krieger. When dealing with the idea that Krieger´s Ritmata was innovative in the context of Brazilian guitar, it seemed necessary to determine which traditions were being broken by the piece. For that, we investigated the formation, the development and the main elements of identity of this repertory. We demonstrate that the language of the piece is connected to concepts of avantgarde, turned to the ideal of universality, which trespasses the barriers of the nationalism largely found in the literature of the Brazilian concert guitar. In order to qualify the piece as avant-garde art, we distinguish some values and concepts that belong to this classification, confronting these ideals with the musical text of the piece. At last, we make a few technical suggestions and point out notes published incorrectly, based on the usual notation of the guitar and in an interview with the composer.